Utilization of Iodine in the Spectrophotometric Determination of Azide and Thiocyanate Anions in Acetonitrile - Ashour, S. (Asian Journal of Chemistry, 2010)
A simple, rapid, accurate and highly sensitive spectrophotometric method for the determination of azide thiocyanate anions in acetonitrile (MeCN) medium is described. The method is based on the formation of yellow colour complexes, l2N3- and l2SCN- , by the reaction of N3- and SCN- anion with iodine in MeCN. Beer's law is obeyed within the concentration range 1.5-21.2 and 0.5-24 μg/mL of N3- and SCN- respectively. A spectrophotometric method has been developed for the titration of azide and thiocyanate anions with iodine in MeCN. The concentration ranges as evaluated by the direct titration are 1.68-22 and 0.58-25.2 μg/mL for N3- and SCN-, respectively. The molar absorptivity, Sandell sensitivity, relative standard deviation and recovery percent are evaluated. The formation constants (log Kf) of the I2SCN- and I2N3- complexes have been evaluated spectro photometrically at 25 ± 0.1 °C as 6.60 ± 0.02 and 6.02 ± 0.03, respectively. Iodide and bromide anions interfere in the determination of thiocyanate and azide anions, transition metals and chloride anion interfere in the determination of thiocyanate and azide, respectively, when present in any percentage.